Three-dimensional PIC/MCC simulation of electron deposition in JAEA 10 A ion sources - 杨超 印茂伟 尚丽平 韦爱勇 (Chinese physics B, 2014)
A systematic research on the electron deposition process in the JAEA 10 A ion source is carried out by using a particle-in-cell/Monte Carlo collision simulation, which is based on a full three-dimensional self-developed code. Two parts are studied. One is the space and energy distribution of fast and slow electrons, the other is the vibration excitation collisions between electrons and hydrogen moleculars. The results show that the inhomogeneity of electrons comes from the Y direction drift of the fast electrons （Te ≥25 eV） due to the action of the magnetic fields. This drift also increases the number of vibration excitation collisions in the -Y direction, and results in the increase of Ha in the -Y direction, eventually leading to the -Y drift of H^-. It explains the spatial non-uniformity in the JAEA 10 A ion source.